Psychosocial Resilience and Quality of Life in Patients with End-Stage Renal Disease Undergoing Hemodialysis: A Cross-Sectional Study - Hassan Zahid; Jehanzaib Islam (Journal of University College of Medicine and Dentistry, 2024)
Objective: To evaluate psychosocial resilience and quality of life (QOL) in patients with end-stage renal disease (ESRD) undergoing hemodialysis at a private hospital in Punjab, Pakistan. Methodology: This cross-sectional study included 191 ESRD patients undergoing hemodialysis at a private center in Lahore, Pakistan, from January to December 2022. Eligible participants were aged 18 or older, diagnosed with ESRD, and receiving regular hemodialysis. Exclusion criteria included acute kidney injury, incomplete medical records, cognitive impairments, or psychiatric disorders. Resilience was measured using the Connor-Davidson Resilience Scale (CD-RISC), and quality of life (QOL) was assessed with the WHOQOL-BREF™ questionnaire. Demographic and clinical data were also collected. Data were analyzed using SPSS version 25.0, with descriptive statistics, one-way ANOVA, and post hoc Bonferroni correction. A p-value of <0.05 was considered statistically significant. Results: The study involved 191 hemodialysis patients with a mean age of 53.4 ± 14.2 years, 45% male and 55% female. Common co-morbidities included hypertension (85%), diabetes (65%), and cardiovascular disease (40%). The mean duration of ESRD was 5.6 ± 3.2 years, with 70% undergoing hemodialysis three times per week. Most patients (60%) had higher education, while 15% had no formal education, and 70% were married. Resilience, measured by the CD-RISC, had a mean score of 45.27 ± 8.35, and QOL, measured by the WHOQOL-BREF™, had a mean score of 51.71 ± 6.30. Both scores were significantly lower than population norms (p = 0.029 for resilience, p = 0.001 for QOL), indicating considerable psychological challenges. Conclusion: ESRD patients on hemodialysis experience low levels of psychosocial resilience and quality of life, highlighting the need for targeted interventions to improve these critical aspects of patient well-being.